SimSchool: A Complex Systems Framework for Simulating Teaching and Learning - Gibson, David (Continuum International Publishing, 2011)
Models of teaching and learning must deal with the complexities of many overlapping and interacting systems. The issues are especially salient when creating computational models, simulations and games that are intended to improve teacher or school leadership education. SimSchool, a network-based training and assessment application for teachers, is an example of a computational model that represents the actions and dynamics of classrooms and offers teachers transferable practice in key instructional planning, diagnostic and interpersonal communication activities. This chapter generalizes from the example of simSchool in order to outline a complex systems framework for simulating teaching and learning.